The Corneoscleral Shell of the Eye: an Age-Related Analysis of Structural Biomechanical Properties. Literature review - E. N. Iomdina; S. Yu. Petrov; A. A. Аntonov; I. A. Novikov; I. A. Pahomova (Oftalʹmologiâ)
Structural biomechanical properties of the ocular corneoscleral shell largely determine its anatomic and optical parameters and its supporting and protective function. Therefore, changes related to age restructuring processes may affect the state of the cornea and the sclera, which should be taken into account in diagnosing eye diseases, especially age-related. According to actual literary data, age-related changes of the corneoscleral shell affecting its biomechanical properties involve all connective tissue components of the extracellular matrix: fibrous proteins (collagen and elastin) and intermediate substance components (proteoglycans and glycosaminoglycans). Aged patients have a larger diameter of elastic fiber fibrils in the external part of the sclera and a lower density of fibrils in the center as compared to young patients, which is an evidence of elastin damage at the molecular level and fibril degeneration. Age-related changes of proteoglycans are primarilymanifested in hydration loss, which leads to an increase in corneal and sclera density and regional thinning of tissues. Agerelated changes of collagen are less expressed than those of elastin and proteoglycans. Yet, the distance between collagen fibrils in the cornea becomes smaller with age; they are subject to destruction, and small spaces devoid of collagen tend to appear in the posterior stroma. The most pronounced age-related degenerative changes of collagen in the deeper layers of the corneal stroma occur in the limb, which accumulates more cross striated collagen fibrils. Recent years of research have shown that the formation of cross-linked chemical bonds, i.e. intra- and intermolecular cross links of collagen is the most important structural factor. It is this particular process that is responsible for structural stability of the corneal and scleral tissue, which tends to change with age or due to certain eye diseases, such as keratoconus or progressive myopia. Obviously, we need clinical technologies that allow an adequate estimation of the biomechanical state of the fibrous shell of the eye.